Th17-Inducing Conditions Lead to in vitro Activation of Both Th17 and Th1 Responses in Behcet's Disease - ALİBAZ ÖNER, FATMA; MUMCU, GONCA; DİRESKENELİ, RAFİ HANER; ERGUN, SAFİYE ATLAS TÜLİN (TAYLOR & FRANCIS INC, 2017)
Objectives: Interleukin-17 (IL-17) has been associated with the pathogenesis of various autoimmune/inflammatory diseases. The aim of this study was to investigate the expression of Th17-related immunity in an innate immunity-dominated vasculitis, namely Behcet's disease (BD). Methods: Peripheral blood mononuclear cells from 37 patients (age: 38.59.8years) with BD, and 25 healthy controls (HC) (age: 39.19.3years), were cultured in Th17-inducing conditions (IL-6, Phytohemagglutinin (PHA), IL-1, and IL-23) for 6days. Cultured cells were stained with CD4, CD8, CD3, TCR gamma/delta, CD19, interferon- (IFN-), and IL-17 antibodies to determine the intracellular cytokine secretion by flow cytometry. Results: IL-17 expression by CD8+ and + T cells was higher in BD compared to HC (p=0.004, p=0.003, respectively). No differences were observed between the groups in the IL-17 production by B cells. Under Th17-inducing conditions, production of IFN- by CD4+, CD8+, and + T cells was also higher in BD compared to HC (p<0.05 in all). Conclusion: Our results suggest that under Th17-stimulating conditions, T cells express both IL-17 and IFN- in BD. More prominent IL-17 and IFN- production by all lymphocyte subsets in BD might be associated with the increased innate responses, early tissue neutrophil infiltrations and late adaptive immunity in BD.
Keywords: Behcet's disease; innate immunity; interleukin-17; Th17 cells; Th1 responses; REGULATORY T-CELLS; GAMMA; UVEITIS; T(H)17